Mu Opioids and Their Receptors: Evolution of a Concept - Pasternak, Gavril W. (The American Society for Pharmacology and Experimental Therapeutics, 2013)
Opiates are among the oldest medications available to manage a number of medical problems. Although pain is the current focus, early use initially focused upon the treatment of dysentery. Opium contains high concentrations of both morphine and codeine, along with thebaine, which is used in the synthesis of a number of semisynthetic opioid analgesics. Thus, it is not surprising that new agents were initially based upon the morphine scaffold. The concept of multiple opioid receptors was first suggested almost 50 years ago (Martin, 1967), opening the possibility of new classes of drugs, but the morphine-like agents have remained the mainstay in the medical management of pain. Termed mu, our understanding of these morphine-like agents and their receptors has undergone an evolution in thinking over the past 35 years. Early pharmacological studies identified three major classes of receptors, helped by the discovery of endogenous opioid peptides and receptor subtypes—primarily through the synthesis of novel agents. These chemical biologic approaches were then eclipsed by the molecular biology revolution, which now reveals a complexity of the morphine-like agents and their receptors that had not been previously appreciated.